1996
DOI: 10.1073/pnas.93.15.7446
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced inactivation of viruses: adsorption of methylene blue, thionine, and thiopyronine on Qbeta bacteriophage.

Abstract: The adsorption of cationic organic dyes (methylene blue, thionine, and thiopyronine) on Qf3 bacteriophage was studied by UV-visible and fluorescence spectroscopy. The dyes have shown a strong affinity to the virus and some have been used as sensitizers for photo-induced inactivation of virus. In the methylene blue concentration range of 0.1-5 ,uM and at high ratios of dye to virus (greater than 1000 dye molecules per virion), the dyes bind as aggregates on the virus. Aggregation lowers the efficiency of photoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 19 publications
0
48
0
1
Order By: Relevance
“…1A), a tricyclic heteroaromatic molecule, has been studied for its intercalative interaction, photoinduced mutagenic actions on binding to DNA, photoinduced inactivation of viruses and as impedance based DNA biosensor [11][12][13][14]. Tuite and Kelly [15] suggested that thionine intercalated and also bound to the outside of linear duplex DNA.…”
Section: Introductionmentioning
confidence: 99%
“…1A), a tricyclic heteroaromatic molecule, has been studied for its intercalative interaction, photoinduced mutagenic actions on binding to DNA, photoinduced inactivation of viruses and as impedance based DNA biosensor [11][12][13][14]. Tuite and Kelly [15] suggested that thionine intercalated and also bound to the outside of linear duplex DNA.…”
Section: Introductionmentioning
confidence: 99%
“…1), a positively charged tricyclic heteroaromatic molecule, has been studied for its photoinduced mutagenic actions [13,14], toxic effects, damage on binding to DNA [15], photoinduced inactivation of viruses [16] and use as an impedance based DNA biosensor [16][17][18][19]. There have been several studies on the toxicity of thionine and many related phenothiazine dyes [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…MB also has potential applications as a photoactive molecule in photodynamics therapy and for the selective killing of bacteria, viruses, and cancerous cells (Jockusch et al, 1996). It is also important to prepare well-ordered MB monolayers on a solid surface due to its potential application as a simple system to study basic aspects of the charge transfer process in enzymes, in high-density device for signal memory, and as templates for the advanced nanopatterning of surfaces.…”
Section: Introductionmentioning
confidence: 99%